2017
DOI: 10.1097/md.0000000000009413
|View full text |Cite
|
Sign up to set email alerts
|

The associations of stroke, transient ischemic attack, and/or stroke-related recurrent vascular events with Lipoprotein-associated phospholipase A2

Abstract: Background:Studies on stroke and lipoprotein-associated phospholipase A2 (Lp-PLA2) have produced conflicting results.Objective:The aim of the study was to assess the associations of Lp-PLA2 levels (mass and activity) with recurrent vascular events in patients with transient ischemic attack (TIA) and/or first ischemic stroke and with stroke in the general population.Methods:The MEDLINE, Embase, the Cochrane Library, Web of Science, Science Direct, China National Knowledge Infrastructure, China Biology Medical D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Lp-PLA2 is produced by macrophages and foam cells in the vascular intima in atherosclerotic plaque, and its biology is linked to the causal pathway of plaque inflammation and ultimate rupture. The serum levels of hs-CRP and Lp-PLA2 are not only risk predictors, but also the key in risk-guided therapy of atherosclerosis diseases [4346]. This study found that the main effects of CAS modeling on the serum levels of hs-CRP and Lp-PLA2 were significant.…”
Section: Discussionmentioning
confidence: 83%
“…Lp-PLA2 is produced by macrophages and foam cells in the vascular intima in atherosclerotic plaque, and its biology is linked to the causal pathway of plaque inflammation and ultimate rupture. The serum levels of hs-CRP and Lp-PLA2 are not only risk predictors, but also the key in risk-guided therapy of atherosclerosis diseases [4346]. This study found that the main effects of CAS modeling on the serum levels of hs-CRP and Lp-PLA2 were significant.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, Lp-PLA2 mass serum levels in the present study were high in stroke patients compared to the controls as demonstrated by recent Tian et al ., a study that showed the association between high, Lp-PLA2 mass serum levels but not Lp-PLA2 activity with the SR.[ 35 ] This is the main reason for selection of Lp-PLA2 mass serum levels but not Lp-PLA2 activity in the present study to evaluate the potential inflammatory role in the ischemic stroke as Lp-PLA2 mass serum levels showed less time-dependent biological variability compared to Lp-PLA2 activity. Moreover, levels of Lp-PLA2 activity are linked with TIA and complicated vascular events whereas; Lp-PLA2 mass levels are more specific and accurate than Lp-PLA2 activity in the association with SR in general populations.…”
Section: Discussionmentioning
confidence: 95%
“…Also, in the general population, high plasma Lp-PLA 2 levels are related to the risk of stroke [ 32 ]. While a higher Lp-PLA 2 activity is related to an enhanced risk for incident PAD, it is more likely that traditional CVD risk factors are more causative [ 7 ].…”
Section: Role Of Phospholipase a 2 In Atheroscleromentioning
confidence: 99%